Mycobacterium paratuberculosis detection in cow's milk in Argentina by immunomagnetic separation-PCR - Gilardoni, Liliana Rosa; Fernández, Bárbara; Morsella, Claudia Graciela; Mendez, Laura Luján; Jar, Ana María; Paolicchi, Fernando; Mundo, Silvia Leonor (Elsevier, 2019)
The aim of this study was to standardize a diagnosis procedure to detect Mycobacterium avium subsp. paratuberculosis (Map) DNA in raw cow milk samples under field conditions. A procedure that combines both immunomagnetic separation and IS900-PCR detection (IMS-IS1 PCR) was employed on milk samples from 265 lactating Holstein cows from Map infected and uninfected herds in Argentina. IMS-IS1 PCR results were analyzed and compared with those obtained from milk and fecal culture and serum ELISA. The extent of agreement between both tests was determined by the Kappa test. IMS-IS1 PCR showed a detection limit of 101 CFU of Map/mL of milk, when 50:50 mix of monoclonal and polyclonal antibodies were used to coat magnetic beads. All of the 118 samples from the Map uninfected herds were negative for the set of the tests. In Map infected herds, 80 out of 147 cows tested positive by milk IMS-IS1 PCR (55%), of which 2 (1.4%) were also positive by milk culture, 15 (10%) by fecal culture, and 20 (14%) by serum ELISA. Kappa statistics (95% CI) showed a slight agreement between the different tests (<0.20), and the proportions of agreement were ≤0.55. The IMS-IS1 PCR method detected Map in milk of the cows that were not positive in other techniques. This is the first report dealing with the application of IMS-IS1 PCR in the detection of Map in raw milk samples under field conditions in Argentina.